Given : roots of a quadratic polynomial 3 + √3 . 3 – √3 To Find : quadratic polynomial Solution: Roots 3 + √3 . 3 – √3 Sum of roots = 3 + √3 + 3 – √3 = 6 Product of roots = (3 + √3 )(3 – √3) = 9 – 3 = 6 quadratic polynomial = x² – (sum of roots)x + product of roots = x² – 6x + 6 x² – 6x + 6 is the required quadratic polynomial whose roots are 3 + root 3 and 3 minus root 3 Learn More: if 2 + root 3 and 2 minus root 3 are the two zeros of the polynomial 2 … brainly.in/question/8973942 if the product of two roots of the equation 4x^4-24x^3+31x^2+6x-8=0 … brainly.in/question/18325992 Reply

Given :roots of a quadratic polynomial3 + √3 . 3 – √3

To Find: quadratic polynomialSolution:Roots

3 + √3 . 3 – √3

Sum of roots = 3 + √3 + 3 – √3 = 6

Product of roots = (3 + √3 )(3 – √3) = 9 – 3 = 6

quadratic polynomial = x² – (sum of roots)x + product of roots

= x² – 6x + 6

x² – 6x + 6 is the required quadratic polynomial whose roots are 3 + root 3 and 3 minus root 3

Learn More:

if 2 + root 3 and 2 minus root 3 are the two zeros of the polynomial 2 …

brainly.in/question/8973942

if the product of two roots of the equation 4x^4-24x^3+31x^2+6x-8=0 …

brainly.in/question/18325992

Answer:x^2-6x+6=0

Step-by-step explanation:hopeitwillhelpu!!!!!andplsfollowme